Inovasi, Adopsi Teknologi, dan Perilaku Kewirausahaan Islami: Sebuah Tinjauan Sistematis - Zainullah, M. Ilham; Ita Marianingsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This systematic review maps how innovation, technology adoption, and Islamic entrepreneurial behaviors are intertwined and contribute to the SDGs. Searches in Scopus followed PRISMA 2020: of the 166 initial records, 46 were eliminated prior to screening; 120 filtered by title–abstract; 45 read in full; and 25 articles were analyzed in depth. Four RQs lead the synthesis: the form of innovation/adoption (RQ1), impact on behavior and performance (RQ2), and their relationship to the SDGs (RQ3). The findings show five complementary faces of innovation: (1) process-organization (knowledge management, open innovation; innovation capability), (2) sharia business/finance models (sharia venture capital, agricultural value chain finance), (3) financial and platform digitalization (fintech, Islamic crowdfunding), (4) technological innovation in business models (e.g., urban farming–aquaponics) that are value-framed, and (5) halal product/marketing innovation (halal assurance and halal trust). Behind that, the drivers are layered: individual values and psychology, Islamic HRM cultural orientation and organizational learning, Islamic finance architecture and regulation, and access to digital literacy and trust in the platform. The impact is multidimensional performance, access to ethical capital, halal market behavior, and social and religious environmental outcomes with strong contributions to SDG 8 and SDG 9, and footprints on SDGs 1–2, 3, 10, 11, 12, 13, 16, 17. This SLR offers an integrated financial innovation value framework and proposes SDGs micro-indicators; limitations mainly in the variation of measurements and the dominance of cross-section designs.